(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The significance and function of export potential lie in its ability to serve as a crucial measure of competitiveness, affirming genuine competitive advantages. Additionally, it acts as an instrument for advancing national interests in the global economic landscape. This article provides a comparative analysis of Uzbekistan’s export potential within the Eurasian Economic Union (EAEU). The article examines foreign trade relationships of Uzbekistan within this regional economic bloc.